2016
DOI: 10.1080/13811118.2016.1211043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Basic Need Satisfaction in the Onset, Maintenance, and Cessation of Non-Suicidal Self-Injury: An Application of Self-Determination Theory

Abstract: The present study applied self-determination theory to examine the onset, maintenance, and cessation of non-suicidal self-injury (NSSI) in adolescents. Specifically, the study examined the relationship between the basic psychological needs of autonomy, competence, and relatedness, and NSSI status. Participants were classified into the NSSI Maintain (n = 30), NSSI Start (n = 44), NSSI Stop (n = 21), or Control (n = 98) groups based on NSSI status over 2 time points within a 12-month period. Repeated measures mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
5
0
2
Order By: Relevance
“…It could be explained by diminished energetic resources resulting from frustrated basic psychological needs and the release or revolt against self-control that can compensate for frustrated psychological needs (Deci & Ryan, 2008; Vansteenkiste & Ryan, 2013). It was also consistent with a previous study that supported the negative link between basic psychological needs satisfaction and non-suicidal self-injury (Emery et al, 2017). From an empirical perspective, non-suicidal self-injury engagement of adolescents whose basic psychological needs are frustrated could be also explained by their depressive and anxiety symptoms (Emery et al, 2015; Liu et al, 2021; Yu et al, 2016; Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It could be explained by diminished energetic resources resulting from frustrated basic psychological needs and the release or revolt against self-control that can compensate for frustrated psychological needs (Deci & Ryan, 2008; Vansteenkiste & Ryan, 2013). It was also consistent with a previous study that supported the negative link between basic psychological needs satisfaction and non-suicidal self-injury (Emery et al, 2017). From an empirical perspective, non-suicidal self-injury engagement of adolescents whose basic psychological needs are frustrated could be also explained by their depressive and anxiety symptoms (Emery et al, 2015; Liu et al, 2021; Yu et al, 2016; Zhu et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Under a selfdetermination theory perspective (Deci & Ryan, 2008), non-suicidal self-injury is a releasing self-control compensatory behavior resulting from diminished energetic resources due to frustrated basic psychological needs (Vansteenkiste & Ryan, 2013). Supporting this view, one previous research study has shown that adolescents who engaged in non-suicidal self-injury report significantly lower levels of basic psychological needs satisfaction compared to adolescents without non-suicidal self-injury engagement (Emery et al, 2017). Empirical evidence also indirectly supported this relation.…”
Section: Basic Psychological Needs Satisfaction As a Mediatormentioning
confidence: 91%
“…Third, this research only explored the mediating role of school engagement and the moderating role of sensation seeking in the relationship between cyberbullying victimization and NSSI among Chinese adolescents, which undermines the cross-cultural generalizability of the conclusions. Future research may consider other mediating variables (e.g., basic psychological needs satisfaction, Emery et al, 2017) and moderating variables (e.g., attachment with peers and parents, Jiang et al, 2017) to further explore the mechanisms between cyberbullying victimization and adolescents' NSSI in eastern and western cultures.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Specifically, a series of k-means cluster analyses were conducted, using the social problems, social competencies, and affective disorders scales of the YSR as clustering variables. Such scales were selected because, on the basis of the results that emerged in previous studies [ 30 , 44 ], we hypothesized that the presence of interpersonal–social difficulties and anxious–depressive symptoms may discriminate between groups with recent and past onset of NSSI. Cluster analyses were conducted on 94 of the 118 NSSI patients because of the missing data in the scales considered (i.e., not all items were answered).…”
Section: Methodsmentioning
confidence: 99%
“…These findings highlighted the predominance of an intrapersonal function in patients with more chronic NSSI (i.e., NSSI lasting more than 12 months), although the frequency of NSSI over the past year, which can be considered a measure of its severity, may play a role in the association between function and duration of NSSI. Emery et al [ 44 ], by conducting a longitudinal study on a sample of 730 adolescents (mean age: 13.4 years), took into consideration the presence of NSSI at two different time points in patients’ history; they found a lower satisfaction of psychological needs (autonomy, competence and relatedness) in the “maintenance” group (NSSI at both time points) compared to the “onset” group (NSSI only in the second time point) and the “cessation” group (NSSI only in the first time point), but a statistically significant difference emerged with the control group (no history of NSSI) only. The authors highlighted that both the “onset” and “cessation” groups were in a transitional period in which needs satisfaction had just begun to change, so additional time would have been necessary to observe the effect of the group membership.…”
Section: Introductionmentioning
confidence: 99%